The Research of Four Sugarcane Variety (Saccharum officinarum ) as The Raw Materials of Bioethanol Production in Negara Bumi Ilir Lampung - M.C. Tri Atmodjo; Agus Eko T; Sigit Setiadi; Nurul Rusdi; Ngatinem JP; . Rina; . Melina; Agus Himawan (International Conference on Engineering and Technology Development (ICETD), 2012)
This research was conducted in order to find out which sugarcane is better between Kidang Kencana, GMP1, GMP2 and PSBM as the raw material for bioethanol production by the application of chemical fertilizer. Four treatment with 3 repetition was done that V1 was Kidang Kencana , V2 was GMP 1, V3 GMP2 and V4 was PSBM 901.. The application of chemical fertilizer got better plant growth, total sugar and juice volume for GMP 2 and Kidang Kencana rather than GMP 1 and PSBM as the raw material for bioethanol production.